Anti-MMP-2 Activity and Skin-Penetrating Capability of the Chemical Constituents from Rhodiola rosea - Lee, Tzong-Huei; Hsu, Chieh-Chih; Hsiao, George; Fang, Jia-You; Liu, Wei-Min; Lee, Ching-Kuo (Planta Medica, 2016)
Based on the significant inhibitory activity toward matrix metalloproteinase-2 and collagenase noticed in preliminary studies, crude extracts of Rhodiola rosea were partitioned and chromatographed sequentially to afford three new compounds, 1,2,3,6-tetra-O-galloyl-4-O-p-hydroxybenzoyl-β-D-glucopyranoside (1), (E)-creoside I (2), and (R,Z)-2-methylhept-2-ene-1,6-diol (3), along with twenty-four known compounds (4–27). Their structures were determined by spectroscopic data analyses. All isolated compounds were subjected to bioactivity assays. In these, 1 specifically inhibited matrix metalloproteinase-2 activity with an IC50 value of 16.3 ± 1.6 µM, while its analogue 1,2,3,6-tetra-O-galloyl-β-D-glucopyranonoside (17) inhibited matrix metalloproteinase-2 with an IC50 value of 23.0 ± 4.8 µM. In the collagenase activity assay, the inhibitory effects of 1 and 17 at concentrations of both 20 and 40 µM were more potent than those of the positive control, 1,10-phenanthroline. In order to realize whether 17 could penetrate from the epidermal layer into the basal and dermal layers of the human skin to inhibit the activity of matrix metalloproteinase-2 and collagenase or not, a transdermal penetration test in nude and white mice skins was performed. Penetration percentages of 17 quantified by LC-MS were 27.8 % and 74.8 % in 24 hours, respectively.
Keywords: Rhodiola rosea; Crassulaceae; matrix metalloproteinase; collagenase; 1,2,3,6-tetra-O-galloyl-4-O-p-hydroxybenzoyl-β-D-glucopyranoside; (E)-creoside I; (Z)-2-methyl-2-hepten-1,6-diol